Processing Differences between Descriptions and Experience: A Comparative Analysis Using Eye-Tracking and Physiological Measures - Glöckner, Andreas; Fiedler, Susann; Hochman, Guy; Ayal, Shahar; Hilbig, Benjamin (Frontiers in Psychology, 2012)
Do decisions from description and from experience trigger different cognitive processes? We investigated this general question using cognitive modeling, eye-tracking, and physiological arousal measures. Three novel findings indeed suggest qualitatively different processes between the two types of decisions. First, comparative modeling indicates that evidence-accumulation models assuming averaging of all fixation-sampled outcomes predict choices best in decisions from experience, whereas Cumulative Prospect Theory predicts choices best in decisions from descriptions. Second, arousal decreased with increasing difference in expected value between gambles in description-based choices but not in experience. Third, the relation between attention and subjective weights given to outcomes was stronger for experience-based than for description-based tasks. Overall, our results indicate that processes in experience-based risky choice can be captured by sampling-and-averaging evidence-accumulation model. This model cannot be generalized to description-based decisions, in which more complex mechanisms are involved.